Novel design and synthesis of a radioiodinated glycolipid analog as an acceptor substrate for N‐acetylglucosaminyltransferase V. (4th September 2013) - Arimitsu, Kenji; Kimura, Hiroyuki; Kajimoto, Tetsuya; Ono, Masahiro; Ohmomo, Yoshiro; Yamashita, Masayuki; Node, Manabu; Saji, Hideo
<x xml:space="preserve">Abstract</x> Guided by the known molecular recognition interactions between N‐acetylglucosaminyltransferase V (GnT‐V) and certain synthetic substrates, we synthesized a radiolabeled double‐stranded glycolipid composed of a long‐chain alkyl unit and a radioiodinated phenylalkyl unit, [125I]‐2‐[N‐(2‐hydroxy‐3‐hexadecyloxy)propyl‐15‐(4‐iodophenyl)pentadecanecarboxamido]ethyl 2‐acetamido‐2‐deoxy‐β‐d‐glucopyranosyl‐(1→2)‐α‐d‐mannopyranosyl‐(1→6)‐β‐d‐glucopyranoside ([125I]2), as a novel intravital glycolipid mimic substrate of GnT‐V. The radioactive iodine (125I) was incorporated via iododestannylation of the phenyltributyltin derivative, 2‐[N‐(2‐acetoxy‐3‐hexadecyloxy)propyl‐15‐(4‐tributylstannylphenyl)pentadecanecarboxamido]ethyl 3, 4, 6‐tri‐O‐acetyl‐2‐acetamido‐2‐deoxy‐β‐d‐glucopyranosyl‐(1→2)‐3, 4, 6‐O‐acetyl‐α‐d‐mannopyranosyl‐(1→6)‐2, 3, 4‐tri‐O‐acetyl‐β‐d‐glucopyranoside (26). Subsequent deacetylation at the final step afforded [125I]2.